HUBUNGAN HIPERTENSI DENGAN FAKTOR RISIKO KELELAHAN KERJA PADA SOPIR TRUK : (STUDI LITERATUR) - Khoirun Nisya; Susilawati Susilawati (CV. ADIBA ADISHA AMIRA, 2023)
Hypertension or high blood pressure is an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg in two measurements with an interval of five minutes in a state of sufficient rest/calm. This can happen because the heart works harder to pump blood to meet the needs of oxygen and nutrients in the body. Hypertension does not cause other diseases. In general, hypertension is an asymptomatic condition, in which abnormally high pressure in the arteries increases the risk of stroke, aneurysm, heart failure, heart attack and kidney damage. Work fatigue is a condition experienced by workers which can result in a decrease in work vitality and productivity. The fatigue factor can cause blood pressure to be higher than normal.